Answers

2016-02-03T11:24:27+05:30
The general term of the series can be given as -3r-2 as the difference is -3 Now the summation of the series -3r-2 , where r is from 1 to 76 can be given as -3[ r(r+1)/2 ] - 2r Substituting value of r as 76, we get -3 [ (76 × 77 )÷ 2] -2×76 = {-3 [ 38×77] -158} = {-3[ 2926] -158} = { -8778-158 } = -8936
0
  • qais
  • Content Quality
2016-02-03T11:43:31+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
It is an AP with a = -5 and d = (-8 -(-5) )= -3
nth term = (a +(n-1)d)
⇒ -230 = -5 + (n-1)×(-3)
⇒ -230 = -5 - 3n + 3
⇒3n =228
⇒n = 76
now, sum = (n/2)(a + nth term)
                 =(76/2)(-5 + (-230))
                 = - 8930
0